The fixed point index for accretive mapping with K—set contraction perturbation in cones - Yu-Qing Chen (International Journal of Mathematics and Mathematical Sciences)
Let P be cone Banach space E, A, K are two mappings in P, A accretive, K is K—set contraction, then fixed point index defined for mapping −A+K, some fixed point theorems are also deduced.